Pengaruh Metode Demonstrasi terhadap Hasil Belajar Siswa pada Mata Pelajaran PAI Materi Wudhu Kelas VII di SMPN 1 Tanjunganom - Laela Adiputri; Elfany Hunafa Salsabilla; Mukhamat Saini (IERA, Islamic Education and Research Academy, 2025)
The objectives of this study are 1) to determine the implementation of the demonstration method in PAI for Grade VII students on the topic of wudhu at SMPN 1 Tanjunganom, 2) the learning outcomes of students in PAI for Grade VII on the topic of wudhu at SMPN 1 Tanjunganom, and 3) the influence of the demonstration method on student learning outcomes in PAI for Grade VII on the topic of wudhu at SMPN 1 Tanjunganom. This study used a quantitative method. The research findings concluded that the questionnaire, used to collect data for the demonstration method variable, was declared reliable because its Cronbach's Alpha value was 0.863 ≥ 0.70. Similarly, the test, used to collect data for the student learning outcomes variable, was declared reliable because its Cronbach's Alpha value was 0.749 ≥ 0.70. Regression analysis results indicated that the demonstration method has a positive relationship with student learning outcomes. Furthermore, based on the T-test analysis, the calculated T-value for variable X was 3.581 > T-table 2.048, and the significance value was 0.001 < 0.05. Therefore, the analysis proves that X influences Y because the significance value of 0.001 < 0.05 means that Ha is accepted, indicating a positive and significant influence of the demonstration method variable on student learning outcomes.